Shoeless Joe & me : a baseball card adventure - Gutman, Dan. (New York : Scholastic, 2002)
Joe Stoshack travels back to 1919, where he meets Shoeless Joe Jackson and tries to prevent the fixing of the World Series in which Jackson was wrongly implicated.
Keywords: Jackson, Joe, -- 1888-1951 -- Fiction; Chicago White Sox (Baseball team) -- History -- Fiction; Time travel -- Fiction; Baseball -- Fiction; Baseball cards -- Fiction